2023
DOI: 10.1167/iovs.64.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Causal Relationships Between Glycemic Traits and Myopia

Abstract: Purpose Little is known about whether sugar intake is a risk factor for myopia, and the influence of glycemic control remains unclear, with inconsistent results reported. This study aimed to clarify this uncertainty by evaluating the link between multiple glycemic traits and myopia. Methods We employed a two-sample Mendelian randomization (MR) design using summary statistics from independent genome-wide association studies. A total of six glycemic traits, including adip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Nevertheless, several plausible explanations can be considered: rstly, chronic in ammatory responses may incite damage and in ammatory reactions in ocular tissues, thereby disrupting the normal structure and function of the retina, optic nerve, and other ocular components, consequently promoting the onset of myopia; secondly, in ammatory responses encompass the release of diverse in ammatory mediators, such as cytokines, chemokines, and in ammatory regulators, which may exert detrimental effects on ocular tissues, such as augmented vascular permeability, cellular apoptosis, brosis, and oxidative stress, ultimately culminating in the development of myopia; thirdly, in ammation is intricately linked to the immune system, and aberrant immune system activation and in ammatory responses may impede normal ocular development and growth, consequently giving rise to myopia; lastly, in ammation-induced vascular alterations and aberrant blood circulation may engender inadequate oxygen supply, nutrient de ciencies, and metabolic disturbances in ocular tissues, thereby impinging upon the normal growth and development of the eye. However, these hypotheses necessitate further experimental investigations to substantiate their validity [53,54].Lastly, we have ascertained a negative correlation between the relative intake of proteins and fats and in ammation. Based on this nding, it is plausible to propose a potential mechanism whereby excessive protein and fat…”
Section: Discussionmentioning
confidence: 80%
“…Nevertheless, several plausible explanations can be considered: rstly, chronic in ammatory responses may incite damage and in ammatory reactions in ocular tissues, thereby disrupting the normal structure and function of the retina, optic nerve, and other ocular components, consequently promoting the onset of myopia; secondly, in ammatory responses encompass the release of diverse in ammatory mediators, such as cytokines, chemokines, and in ammatory regulators, which may exert detrimental effects on ocular tissues, such as augmented vascular permeability, cellular apoptosis, brosis, and oxidative stress, ultimately culminating in the development of myopia; thirdly, in ammation is intricately linked to the immune system, and aberrant immune system activation and in ammatory responses may impede normal ocular development and growth, consequently giving rise to myopia; lastly, in ammation-induced vascular alterations and aberrant blood circulation may engender inadequate oxygen supply, nutrient de ciencies, and metabolic disturbances in ocular tissues, thereby impinging upon the normal growth and development of the eye. However, these hypotheses necessitate further experimental investigations to substantiate their validity [53,54].Lastly, we have ascertained a negative correlation between the relative intake of proteins and fats and in ammation. Based on this nding, it is plausible to propose a potential mechanism whereby excessive protein and fat…”
Section: Discussionmentioning
confidence: 80%
“…These studies may be affected by confounding factors such as education level and outdoor exposure. A previous Mendelian randomization study found a causal relationship between adiponectin, HbA1c and myopia, where low adiponectin levels and high HbA1c can increase the risk of myopia 24 . However, the study did not adjust for confounding factors such as BMI using multivariate Mendelian randomization, so its results require further validation.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, some studies have found that young adult men with low BMI have a higher incidence of myopia 28 , while others believe that there is no relationship between BMI and myopia [29][30] .The reason for these discrepancies in research may be that some studies did not include factors such as screen time exposure, outdoor time, dietary habits, and physical activity habits, and different studies may also be in uenced by race and regional factors. The Mendelian randomization study by Li et al did not nd a causal relationship between BMI and myopia 24 . This is inconsistent with our current research result that BMI is an important protective factor for myopia.…”
Section: Discussionmentioning
confidence: 93%
“…While the IVW method is widely used, researchers should also consider sensitivity analyses and other methods, such as weighted median and MR-Egger regression, to assess the robustness of results and detect potential violations of assumptions. Therefore, results from MR were deemed meaningful if the IVW method identified a significant association ( p < 0.05), and concordantly, two additional methods, MR-Egger regression and weighted median (WM), also indicated effects in the same direction ( Li FF et al, 2023 ).…”
Section: Methodsmentioning
confidence: 98%
“…A higher F-statistic indicates a stronger instrument. Moreover, our analysis was constrained to results derived from a minimum of three shared SNPs ( Li FF et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%